Kajian UU 11/2020 tentang Cipta Kerja Klaster Ketenagakerjaan: Studi pada Regulasi Pengupahan, PHK, dan Pesangon - Fajar B Hirawan; Adinova Fauri; Henriko Tobing; Muhyiddin Muhyiddin (Jurnal Ketenagakerjaan, 2023)
Several aspects concern the attention of labor and employer on Constitution Number 11, the Year 2020, under Job Creation Act. Initially, worries arise about the possibility of one-sided layoffs. Layoff often occurs through companies that have yet to have a discussion. Nevertheless, it is necessary to align that the layoffs mechanism, in brief, does not intend to promote one-sided layoffs by employers. Under the Job Creation Act, Article 151 provided the bases for stakeholders to prevent any layoff. Further Constitution yet gives the possibility of a chance if employees are offended by any employer's treatment. In brief, this mechanism covers appreciates, protects, and supports employment rights fulfillment. In other words, this mechanism is still based on equity. Secondly, there is no further appropriate explanation concerning the reduction of wage policy in the Job Creation Act, whereas it is relevant for employment. The revision in Wage Policy includes reformation effort in severance pay, which also includes affirmation effort in share effect as risk management means, such as the risk of unemployment. Such matter needs further study empiric that shows whether the multiplier number as listed in Job Creation Act Constitution, which is Government Regulation No. 35 the Year 2021, is at an ideal level or not (or corresponds with employer capability). Third, there is no doubt that severance pay implementation can not avoid Labor Union attention. For instance, Labor/employee object if said severance pay is easily accepted. According to them, this dispute often occurs in Industrial Relations Court. Hence, the successful, effective implementation of a new severance pay policy indicates a strengthened Social Security. Regarding this, there are a few notes on implementation. For instance, to ensure corresponding data of Health BPJS and employment BPJS.